Protein import into mitochondria: the requirement for external ATP is precursor-specific whereas intramitochondrial ATP is universally needed for translocation into the matrix. - Wachter, C (Mol Biol Cell, 1994)
ATP is needed for the import of precursor proteins into mitochondria. However, the role of ATP and its site of action have been unclear. We have now investigated the ATP requirements for protein import into the mitochondrial matrix. These experiments employed an in vitro system that allowed ATP levels to be manipulated both inside and outside the mitochondrial inner membrane. Our results indicate that there are two distinct ATP requirements for mitochondrial protein import. ATP in the matrix is always needed for complete import of precursor proteins into this compartment, even when the precursors are presented to mitochondria in an unfolded conformation. In contrast, the requirement for external ATP is precursor-specific; depletion of external ATP strongly inhibits import of some precursors but has little or no effect with other precursors. A requirement for external ATP can often be overcome by denaturing the precursor with urea. We suggest that external ATP promotes the release of precursors from cytosolic chaperones, whereas matrix ATP drives protein translocation across the inner membrane. IMAGES: